The role of installation artists in Expressing contemporary issues (Al-Academy, 2024)
The ability of the contemporary artist to express issues, events, crises, disasters and wars has been evident since the first practices of art throughout history. When postmodern art appeared, it provided artists with different methods and implementations than were previously used; artists were able to employ the techniques and technology provided by the era, and this contributed greatly to highlighting the aesthetics of the artwork and its expressive values.The current research came to shed light on the role of installation artists in expressing the issues experienced by the world and the changes that societies are witnessing. By tracing the most important practices of the art of installation in space as one of the contemporary trends that enabled the artist to aesthetically express a huge amount of ideas in a contemporary visual form. The research follows the historical method by tracing the historical roots of installation arts. As well as the analytical descriptive approach to analyze a group of artistic practices that employ the art of installation in contemporary artwork, and the most important issues and events that surround this artwork.The research concluds that the installation art of has great potentials in linking the artist's ideas to the issues and events that revolve around him. The ability of the installation artists in appears in linking the form and content when expressing the issues in a contemporary artistic form with the artistic and aesthetic values ​​of the concept of the installation art. The research recommends making more effort to reach the most important contemporary artistic practices and trends that deal with the most important global issues and events in a contemporary artistic style.